MODEL PENGAMBILAN KEPUTUSAN PARTISIPATORIS UNTUK e-PARTICIPATION DENGAN PENDEKATAN SOCIOTECHNICAL (STUDI KASUS: MUSRENBANG) - , Vitri Tunjungsari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research proposes a model to support participatory group decision making for eParticipation. The model does not use multi-criteria decision making technique nor a voting rule. Instead, the model employs socio-technical approach, i.e.: trust model and consensus achievement to facilitate judgment and decision process. The setting of group decision making here comprises of decision maker varied from expert to novice with no former knowledge to decide on certain alternatives. This is also known as participatory approach in decision making. The objectives of this research are (1) to produce a public participatory decision making model for e-Participation via the identification of e-Participation criteria and variable from socio-technical perspectives and the identification of public group decision making characteristics